Association between serum β-carotene and suicidal ideation in adults: a cross-sectional study - Lv, Jihua; Xu, Tong; Lou, Shuyue; Zhan, Zhenxiang; Cheng, Zicheng; Fu, Fangwang (Frontiers in Nutrition, 2024)
BackgroundThe aim was to ascertain whether serum carotenoid levels are linked to suicidal ideation, along with how depressive disorder influences the association.MethodsThis research was conducted using a cross-sectional design and encompassed 7,335 adults from the United States. The levels of serum carotenoids, encompassing α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein/zeaxanthin, were ascertained by employing high-performance liquid chromatography. Item nine of the nine-item Patient Health Questionnaire was used to evaluate suicidal ideation. The study used multivariable-adjusted logistic regression and restricted cubic spline models to ascertain the link between serum carotenoid levels and suicidal ideation. Mediation and stratified analyses were used to ascertain the impact of depressed symptoms on the association between serum carotenoid levels and suicidal ideation.ResultsOut of the total participants, 245 individuals (3.3%) reported having suicidal ideation. Participants who had suicidal ideation showed lower levels of serum α-carotene, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin compared to those who did not have suicidal ideation. After controlling potential confounding factors, serum β-carotene level was still associated with risk of suicidal ideation (per 1–standard deviation (SD) increment, odds ratio [OR]: 0.73, 95% confidence interval [CI]: 0.55–0.98). The mediation analysis revealed that 36.3% of this association was mediated by the severity of depressive symptoms. Stratified analysis manifested that the association remained in depressed people but was attenuated in people without depressive disorder.ConclusionIncreased serum β-carotene level may decrease the susceptibility to suicidal ideation, especially in depressed people. Further intervention studies are needed to validate whether β-carotene consumption contributes to preventing suicidal ideation.